PROSPECTS OF SOCIAL INVESTMENT DEVELOPMENT IN THE BANKING SECTOR - Тяжкороб, Ірина; Марканич, Тетяна (Socio-economic relations in the digital society, 2019)
The directions of development of social investing in domestic banks are presented taking into account foreign experience. Areas of development of social investment in domestic banks include a number of measures at the macroeconomic level of management (improvement of the mechanism of state regulation of the process of social investment); at the mesoeconomic level (improvement of the mechanism of interaction between state, regional authorities and business structures, in particular banks) and microeconomic level (improvement of the mechanism of social investment at the level of the banking structure). Emphasis is placed on the need to improve the regulatory framework for regulating investment activity in the light of current trends in the world, including the improvement of tax legislation on charity; adoption of the draft document "Concept of the National Strategy for Corporate Social Responsibility in Ukraine"; adoption of uniform standards for non-financial reporting by entities that meet international standards; development and adoption by the government of a concept and action plan for the implementation of the green bond market. It is emphasized that in order to increase the efficiency of corporate social responsibility management of banks, it is advisable to further implement the principles of corporate social responsibility, to increase the level of disclosure of information on corporate social responsibility; expand the list of banks’ financial services, taking into account social and environmental factors based on current domestic and international experience. New models of partnership in the implementation of social investing are conducting social projects contests, implementation of corporate volunteer programs, development of social entrepreneurship, impact investing.